2012
DOI: 10.1186/1748-717x-7-222
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated radiotherapy for primary or secondary oligometastatic lung cancer using Tomotherapy

Abstract: BackgroundTo retrospectively review the outcome of patients with primary or secondary oligometastatic lung cancer, treated with hypofractionated Tomotherapy.MethodsBetween April 2007 and June 2011, a total of 33 patients with oligometastatic intrapulmonary lesions underwent hypofractionated radiotherapy by Tomotherapy along with appropriate systemic therapy. There were 24 primary, and 9 secondary lung cancer cases. The radiation doses ranged from 4.5 to 7.0 Gy per fraction, multiplied by 8–16 fractions. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Despite increasing understanding of the molecular mechanism of cancers 2, 3, many malignancies remain resistant to established traditional treatments 4, 5. However, the definition of tumor-associated genetic mutations has heightened interest in cancer treatment as the target for gene therapy 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing understanding of the molecular mechanism of cancers 2, 3, many malignancies remain resistant to established traditional treatments 4, 5. However, the definition of tumor-associated genetic mutations has heightened interest in cancer treatment as the target for gene therapy 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…According to a report on radiotherapy for patients with oligometastatic lung cancer, the median survival in those with two or fewer metastatic foci was 40 months or more, whereas that in those with three or more metastatic foci was 26 months. 7 In the present case, there were five metastatic foci (vagina: one, lungs: four). Considering this, close follow-up may be necessary in the future, although there has been no relapse during the 36-month follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…In non–small‐cell lung cancer (NSCLC) or CRC oligometastases, SBRT is well tolerated and provides favorable local control (LC) and OS . Some studies have showed hypofractionated stereotactic radiotherapy delivered with less than five fractions can significantly improve outcomes . The efficacy of irradiation therapy is dose‐dependent, with higher doses tending to provide better responses .…”
Section: Introductionmentioning
confidence: 99%
“…13,16 Some studies have showed hypofractionated stereotactic radiotherapy delivered with less than five fractions can significantly improve outcomes. 17,18 The efficacy of irradiation therapy is dose-dependent, with higher doses tending to provide better responses. [19][20][21] The aim of this study was to review the outcomes of CRC oligometastases treated with hypofractionated stereotactic radiotherapy at our institution and determine the effect of BED on outcomes.…”
Section: Introductionmentioning
confidence: 99%